Effects of task complexity and sensory conflict on goal-directed movement - Serrien, Deborah J.; Spapé, Michiel M. (Elsevier, 2009)
Interactions between brain regions are necessary for compound activities to take place. Accordingly, evaluating hemispheric information processing during skilled behaviour provides valuable knowledge about brain regulation. To this end, the present study assessed the neural changes in response to task complexity and visuomotor discrepancy during motor (drawing) actions. EEG phase synchronization, expressing interregional communication, showed that visuomotor discordance perturbed information processing across both hemispheres, whereas task complexity induced pronounced adjustments in the left (dominant) hemisphere. However, the effects of task complexity and sensorimotor conflict interacted, and suggested that the main process of spatiotemporal integration was localized within the left hemisphere. Furthermore, a significant association between left hemisphere couplings and performance accuracy proposed that connectivity strength and behavioural output are linked with one another. These results suggest that functional connectivity patterns provide higher-order associations for information coding during skilled actions.